2011
DOI: 10.3168/jds.2011-4219
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Listeria monocytogenes introduced as a post-aging contaminant during storage of low-salt Cheddar cheese at 4, 10, and 21°C

Abstract: Traditional aged Cheddar cheese does not support Listeria monocytogenes growth and, in fact, gradual inactivation of the organism occurs during storage due to intrinsic characteristics of Cheddar cheese, such as presence of starter cultures, salt content, and acidity. However, consuming high-salt (sodium) levels is a health concern and the dairy industry is responding by creating reduced-salt cheeses. The microbiological stability of low-salt cheese has not been well documented. This study examined the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
6
33
2
1
Order By: Relevance
“…It was in the same range than those found in Cantal cheeses by De Freitas et al (2007). As discussed by Wemmenhove et al (2013) and by Shrestha, Grieder, McMahon, and Nummer (2011), such concentrations alone cannot affect the behaviour of L. monocytogenes.…”
Section: Physico-chemical and Organic Acid Changesmentioning
confidence: 95%
“…It was in the same range than those found in Cantal cheeses by De Freitas et al (2007). As discussed by Wemmenhove et al (2013) and by Shrestha, Grieder, McMahon, and Nummer (2011), such concentrations alone cannot affect the behaviour of L. monocytogenes.…”
Section: Physico-chemical and Organic Acid Changesmentioning
confidence: 95%
“…There was no significant difference in pH between reduced and regular sodium Mozzarella cheeses stored at 4 and 12 °C at either 90 or 30 days (Table 2-10). 14 log CFU/g in low and standard salt Cheddar cheese (0.7% and 1.8%), with a pH similar to this study, stored at 4, 10, and 21 °C, respectively (Shrestha et al, 2011a). However, the salt concentration and cheese type used differed from the present study, which caused a significantly higher reduction at higher temperatures.…”
Section: Resultscontrasting
confidence: 55%
“…Other researchers also studied the fate of L. monocytogenes and Salmonella in low (0.7 %) and regular (1.8 %) Cheddar cheese. Listeria monocytogenes and Salmonella counts gradually decreased for each treated cheese regardless of salt concentration (Shrestha et al 2011a ;Shrestha et al, 2011b). However, Hystead et al (2013) reported that L. monocytogenes inoculated in Cheddar cheese after two and three weeks of cheese aging survived and grew better in low sodium (between 1.26 to 1.65%) cheese compared to regular sodium Cheddar cheese during storage day at 4 °C, but growth was not enhanced at 12°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…monocytogenes survived for 90, 90 and 30 days in cheddar cheese when incubated at 4°, 10° and 21°C, respectively (Shrestha et al, 2011a). No decrease in L. monocytogenes counts was observed over the 12 day incubation at 10°C when the organism was artificially inoculated into cuajada, a semisolid dairy product (Arques et al, 2008a).…”
Section: Pathogen Growth and Survival In Cheesementioning
confidence: 97%